Análise da obesidade entre adolescentes e a correlação com o estado do condicionamento físico em escolas públicas na cidade de Franca- SP - Rodrigues, Maicon Romano (2015)
Defined as a chronic disease, through accumulation of body fat in relationship to lean body mass, obesity promotes metabolic and structural changes in the body, and its physiognomy, often bringing harm to the individual.It has beengrowing significantly also it has become one of the major health problems in the world. Obesity is represented by the group Chronic Non-Communicable Disease (CNCD), whether as a chronic disease, non-infectious, degenerative, or non-communicable chronic, the latter being the most used. Among the factors that determine the (CNCD), we have lifestyle (habits and behaviors) the work environment (occupational diseases) that cause some risk of disease, and various factors such as sedentary lifestyle, obesity, smoking and alcohol. The consequences related to obesity among children and adolescents have become prevalence of incidence, related to disease associated with overweight appears early as joint problems in bones and bringing many problems over the years. This study aimed to identify and correlate indexes prevalence of obesity and indicators of physical fitness status among adolescentes both genders, aged 11 to 15 years, in the city of Franca, Brazil. Regarding the distribution of anthropometric (BMI) values to the range age of 11 and 12 years, were classified 31.2% and overweight 9.3% as obese and 21.05% and overweight 13% as obese for male and female respectively. For the age group of 13 and 14 years, were classified 16.6% overweight 3.4% and obese 9.3% and overweight 12.5% obese.